Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
expanding brackets?? b (b-4)?
hey, i just need a little help, im just confused about the minus part
b (b - 4 ) =
is it b^2 +4
11 Answers
- 9 years ago
No, that's not quite right. If we expand the bracket, then we would have to multiply b with b and then b with negative 4:
b(b-4)=
b^2 - 4b
As you can see, the 4 has a minus sign in front, so multiplying a positive letter by a negative number, we get a negative answer.
Hope this helps.
- Anonymous9 years ago
You just distribute the thing outside parenthesis to the terms inside.
b(b - 4) = b(b) - b(4) = b^2 - 4b.
Hope this helps :)
- How do you think about the answers? You can sign in to vote the answer.
- 9 years ago
just multiply everything inside bracket by number out side.
ie b^2 -4b
now if you had -b(b-4) answer would be -b^2 + 4b because you are multiplying by -b
- 9 years ago
You need to time everything inside the brackets by what is outside so
bxb and 4xb
so b^2-4b
- 9 years ago
Hi, no it would be b squared - 4 because there's a minus sign infront of the 4 making it b*-4
- LuisLv 69 years ago
Dear Up All N!ght 182,
b(b-4)
Multiply b by each term inside the parentheses (b-4).
b(b)+b(-4)
Multiply b by the b inside the parentheses.
b*b+b(-4)
Multiply b by b to get b^(2).
b^(2)+b(-4)
Multiply b by the -4 inside the parentheses.
b^(2)-b*4
Multiply -b by 4 to get -4b.
b^(2)-4b
======================
Who am I, ldiazmdiaz, learn more...
http://www.youtube.com/results?search_query=kc9byk...
======================
Thanks
Source(s): Precalculus Solved!